Adolescents snacks: fruit and vegetable consumption - Alves, Ana Isabel Pereira (2016)
The snack meal is defined as the consumption of food ingested in addition to the three main meals, and thereby contributing to additional calories. Increasing the number of snacks may be beneficial, as long as the energy balance is maintained, and are frequently mentioned as an opportunity to increase fruit consumption, however, carbohydrates and added sugars tend to be over-consumed at snacking occasions.The aim of this study was to evaluate the relationship between the prevalence of snack consumption and fruits and vegetables intake in adolescents. A sample of 70 adolescents between 12 and 19 years was studied. The adolescents were assessed for snacks consumption through the three day food diary method and their anthropometric data were objectively measured. Data analysis was performed with the ordinal Spearman correlation test, with a 95% significance, using the SPSS 22.0. Adolescents had a mean of 4.4 meals and 1.5 snacks a day. There was a positive correlation between fruit and vegetables consumption and the prevalence of snacks, the same was observed for the total number of meals and the consumption of vegetables. These results were in agreement to what has been shown by Marques Vidal et al (2006), also regarding Portuguese adolescents. These results suggest that the higher the prevalence of snack consumption, the greater the consumption of fruits and vegetables, signifying a positive relation between snacking and a healthy diet.